Learning Management of the Taklim Council in Improving Understanding of Islam in West Java Province - Siti Saodah Susanti; Engkus Kuswarno; Kingking Muttaqien; R. Supyan Sauri (Journal of Social Science, 2021)
This study aims to determine the curriculum, program, materials, implementation of learning, professionalism asatidz, methods, media, management, financial management, obstacles, and the role of majelis taklim in increasing understanding of Islam in West Java Province. The subjects of this study were the Bandung Regency Conventional Taklim Council and the Bandung City Diniyah Al-Ikhlas Conversion Taklim Council. The method used is qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that there are differences in learning management applied in the two taklim assemblies. The Conventional Taklim Assembly of Asy-Syujaiyah Bandung Regency still uses the traditional learning system, while the Diniyah Conversion Taklim Council is the learning system for semi-formal ones